Art and visual perception a psychology of the creative eye - Arnheim, Rudolf (University of California Press, 1974)
Since its first publication in 1954, this work has established itself as a unique classic. It applies the approaches and findings of modern psychology to the study of art: it describes the visual process that takes place when people create- or look at- works in the various arts, and explains how the eye organizes visual material according to definite psychological laws. Fresh in thought, clean in style, this book is a highly readable contribution to the study of aesthetics. It could be recommended as an excellent introduction to the psychology of perception, however, it is the art lover, whether psychologist or not, who will find this book the most rewarding."--from Book Jacket.